2012
DOI: 10.2341/11-337-c
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Comparative Study of the Effectiveness of and Tooth Sensitivity to 10% and 20% Carbamide Peroxide Home-use and 35% and 38% Hydrogen Peroxide In-office Bleaching Materials Containing Desensitizing Agents

Abstract: The aim of this study was to compare the effectiveness of and tooth sensitivity to 10% and 20% carbamide peroxide (CP) home-use bleaching agents and 35% and 38% hydrogen peroxide (HP) in-office bleaching agents, all of which contain desensitizing agents, in a clinical trial. Four agents were evaluated: 10% CP and 20% CP (Opalescence PF 10% and Opalescence PF 20%, Ultradent, both with 0.5% potassium nitrate and 0.11% fluoride ions), 38% HP (Opalescence Boost PF, Ultradent, with 3% potassium nitrate and 1.1% flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
188
2
24

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(226 citation statements)
references
References 22 publications
12
188
2
24
Order By: Relevance
“…21 Additionally, it may also reduce the pulp-reparative capacity 22 and induce pulp inflammation, which may be responsible for the TS experienced by the patients during in-office bleaching. 1 All three participants from this study experienced moderate to considerable TS that decreased to a mild level one week after bleaching. The literature usually reports that TS normally persists for up to four days after bleaching, 2 but durations of up to 39 days have been reported.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…21 Additionally, it may also reduce the pulp-reparative capacity 22 and induce pulp inflammation, which may be responsible for the TS experienced by the patients during in-office bleaching. 1 All three participants from this study experienced moderate to considerable TS that decreased to a mild level one week after bleaching. The literature usually reports that TS normally persists for up to four days after bleaching, 2 but durations of up to 39 days have been reported.…”
Section: Discussionmentioning
confidence: 75%
“…The patients are instructed to wear the bleaching tray daily, for periods ranging from 1 to 8 h from 2 to 6 weeks. 1 In spite of the safety and effectiveness of this technique to whiten teeth, some patients do not want to use the trays even for shorter periods of time. In this clinical scenario, in-office bleaching using higher concentrations Declaration of Interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with that documented by Zeknois et al, who reported that HB produced significantly lighter teeth than in-office bleaching during all active treatment periods and follow-up visits (10). However, most other bleaching studies conducted in Caucasian populations have reported both HB and OB to be equally effective (9,(13)(14)(15)(16)(17)(18)(19). The disparity in findings may be attributed to differences in bleaching agent concentrations, total treatment time, and racial variance of human teeth (20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…Most clinical trials on dental bleaching have been conducted on Caucasian populations (9,(13)(14)(15)(16)(17)(18)(19). However, racial differences in tooth anatomy, dimensions, and translucency may influence the outcomes of dental bleaching (20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%